Changes in Internalized Stigma and HIV Health Outcomes in Individuals New to HIV Care: The Mediating Roles of Depression and Treatment Self-Efficacy - Yigit, Ibrahim (AIDS Patient Care STDS, 2020)
There is limited research on the effects of stigma on health outcomes among new-to-HIV care individuals. We examined the effect of changes in internalized stigma over time on health behaviors and outcomes such as viral suppression, antiretroviral therapy (ART) adherence, and visit adherence among new-to-HIV care individuals. We also analyzed the mediating effects of adherence self-efficacy and depressive symptoms in these associations. Participants were 186 persons living with HIV who initiated care at four HIV clinical sites in the United States and had diverse geographical and ethnic backgrounds. Baseline and 48-week follow-up assessments included measures of internalized stigma, ART adherence, depressive symptoms, and adherence self-efficacy. HIV visit adherence and viral load data were extracted from clinic records. Age, race, gender, insurance status, and site were controlled in all analyses. Logistic regression analyses were used to examine predictors of adherence and viral suppression. Change (decrease) in internalized stigma was calculated by subtracting follow-up internalized stigma scores from baseline scores and served as the main predictor. Mediation analyses included calculation of 95% confidence intervals for the indirect effects using bootstrapping. Decreases in internalized stigma over time were positively associated with viral suppression, ART adherence, and visit adherence. Adherence self-efficacy significantly mediated these effects of decrease in internalized stigma on all outcomes. Depressive symptoms only mediated the association between decrease in internalized stigma and ART adherence. Interventions that address internalized stigma and depressive symptoms, as well as adherence self-efficacy, may significantly improve adherence and viral suppression outcomes for individuals new to HIV care.